On Long Cycles in Digraphs with the Meyniel-type Conditions - Darbinyan, S.; Karapetyan, I. (Mathematical Problems of Computer Science, 2021)
We shall assume that the reader is familiar with the standard terminology on directed graphs (digraphs) and use Bang-Jensen and Gutin [1] as reference for undefined terms. In this paper we consider finite digraphs without loops and multiple arcs. The subdigraph of D induced by a subset A of V(D) is denoted by (A). We will denote the complete bipartite digraph with partite sets of cardinalities p, q by K*p,q.